2017
DOI: 10.1007/s12038-017-9722-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-876-5p suppresses epithelial–mesenchymal transition of lung cancer by directly down-regulating bone morphogenetic protein 4

Abstract: Lung cancer is the leading cause of cancer-related death throughout the world. We aimed to investigate the role of a novel microRNA-876-5p and its potential molecular target bone morphogenetic protein 4 (BMP-4), in the epithelial-mesenchymal transition (EMT) of lung cancer. Expressions of microRNA-876-5p and its potential target BMP-4 were analysed in lung cancer cells and patient tissues. Luciferase activity assay was conducted to verify direct targeting of microRNA- 876-5p to the 3'-UTR of BMP-4 mRNA. Migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…MiR‐876‐5p restricted the aggressive behaviors of hepatocellular carcinoma (HCC) . MiR‐876‐5p had suppressive activity against lung cancer . Nevertheless, miR‐876's effect on GC has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…MiR‐876‐5p restricted the aggressive behaviors of hepatocellular carcinoma (HCC) . MiR‐876‐5p had suppressive activity against lung cancer . Nevertheless, miR‐876's effect on GC has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…That data suggest a tumour suppressive role for miR‐876‐5p in cancer progression. Indeed, this tumour suppressive function is evidenced in a wide range of cancers, including lung cancer, esophageal squamous cell carcinoma, head and neck squamous cell carcinoma, hepatocellular carcinoma, gastric cancer, and breast cancer . However, whether miR‐876‐5p is involved in colorectal cancer remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this tumour suppressive function is evidenced in a wide range of cancers, including lung cancer, esophageal squamous cell carcinoma, head and neck squamous cell carcinoma, hepatocellular carcinoma, gastric cancer, and breast cancer. 28,29,[33][34][35][36] However, whether miR-876-5p is involved in colorectal cancer remains undetermined. Here, our results demonstrated that miR-876-5p was decreased in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…11 MiR-613 inhibits OS cell proliferation and migration, and induces apoptosis by targeting chemokine receptor 4 (CXCR4). 13 Recently, A new tumour-suppressive miR-876-5p has been found to play important roles in a variety of tumours including lung cancer, 14 oesophageal squamous cell carcinoma (ESCC), 15 hepatocellular carcinoma (HCC) 16,17 and head and neck squamous cell carcinoma (HNSCC). 13 Recently, A new tumour-suppressive miR-876-5p has been found to play important roles in a variety of tumours including lung cancer, 14 oesophageal squamous cell carcinoma (ESCC), 15 hepatocellular carcinoma (HCC) 16,17 and head and neck squamous cell carcinoma (HNSCC).…”
mentioning
confidence: 99%
“…13 Recently, A new tumour-suppressive miR-876-5p has been found to play important roles in a variety of tumours including lung cancer, 14 oesophageal squamous cell carcinoma (ESCC), 15 hepatocellular carcinoma (HCC) 16,17 and head and neck squamous cell carcinoma (HNSCC). 14,16,18 Moreover, miR-876-5p suppresses tumour growth and metastasis of ESCC by targeting tumour antigen MAGE-A family. 14,16,18 Moreover, miR-876-5p suppresses tumour growth and metastasis of ESCC by targeting tumour antigen MAGE-A family.…”
mentioning
confidence: 99%